Spatial Distribution of Marine Tourism Objects in Leitimur Selatan District, Ambon City - Marhelin C Mehdila; Daniel A Sihasale; Susan E. Manakane; Heinrich Rakuasa (Tinta Emas Publisher, 2023)
This study aims to analyze the spatial distribution of marine tourism objects in the South Leitimur District, Ambon City. Knowledge of this spatial distribution is essential in developing sustainable regional marine tourism. Spatial mapping methods and Geographic Information System (GIS) analysis are used to identify and map locations and distribution of marine tourism objects. The study results show five tourist objects in South Leitimur District: Namasua Beach, Nanseri Beach, Hukurila Beach, Batu Lubang Lima Beach, and Lawena Beach. The benefit of this research is to provide critical information for decision-making in developing marine tourism. The government and tourism actors can use the results of this mapping to plan tourism infrastructure development, allocate resources more efficiently, and design more effective marketing strategies. In addition, this research also provides an understanding of the need for sustainable natural resource management to maintain the sustainability of existing marine tourism objects.